Comparative Analysis of Different Isolated Oleaginous Mucoromycota Fungi for Their γ-Linolenic Acid and Carotenoid Production. (6th November 2020) - Mohamed, Hassan; El-Shanawany, Abdel-Rahim; Shah, Aabid Manzoor; Nazir, Yusuf; Naz, Tahira; Ullah, Samee; Mustafa, Kiren; Song, Yuanda
Abstract : γ -Linolenic acid (GLA) and carotenoids have attracted much interest due to their nutraceutical and pharmaceutical importance. Mucoromycota, typical oleaginous filamentous fungi, are known for their production of valuable essential fatty acids and carotenoids. In the present study, 81 fungal strains were isolated from different Egyptian localities, out of which 11 Mucoromycota were selected for further GLA and carotenoid investigation. Comparative analysis of total lipids by GC of selected isolates showed that GLA content was the highest in Rhizomucor pusillus AUMC 11616.A, Mucor circinelloides AUMC 6696.A, and M. hiemalis AUMC 6031 that represented 0.213, 0.211, and 0.20% of CDW, respectively. Carotenoid analysis of selected isolates by spectrophotometer demonstrated that the highest yield of total carotenoids (640 μ g/g) was exhibited by M. hiemalis AUMC 6031 and M. hiemalis AUMC 6695, and these isolates were found to have a similar carotenoid profile with, β -carotene (65%), zeaxanthin (34%), astaxanthin, and canthaxanthin (5%) of total carotenoids. The total fatty acids of all tested isolates showed moderate antimicrobial activity against Staphylococcus aureus and Salmonella Typhi, and Penicillium chrysogenum . To the best of our knowledge, this is the first report on the highest yield of total lipid accumulation (51.74% CDW) by a new oleaginous fungal isolate R. pusillus AUMC 11616.A. A new scope for a further study on this strain will be established to optimize and improve its total lipids with high GLA production. So, R. pusillus AUMC 11616.A might be a potential candidate for industrial application.